Development of Rubber Substrate for More Robust Flexible Wearable Antenna at 2.4 GHz Application - Rahmad, Farisha Eriena; Mohamad, Sarah Yasmin; Abdul Malek, Norun Farihah; Abd Rahman, Faridah; Ruslan, Ahmad Alhadi; Zainal, Nurfarina (IEEE, 2021)
In this work, a flexible microstrip patch antenna has been designed to be working at 2.4 GHz using rubber as the substrate material with permittivity of 3.0 and loss tangent of 0.02. The proposed antenna has been designed to achieve a good result of reflection coefficient, vswr, gain, directivity, and antenna efficiency at the selected operating frequency. The design of rectangular microstrip flexible antenna with two-element horizontal array has depicted a positive performance for wireless frequency band specifically at 2.4 GHz. The selected design has achieved a return loss of -49.659 dB, VSWR of 1.007, gain of 8.16 dBi, directivity of 9.21 dBi and 78.5% of total antenna efficiency. The proposed design is expected to be able to complement with the wearable innovation such as technology used on human body and is applicable for basic communication applications.